Paediatric Hypertension in Africa: A Systematic Review and Meta-Analysis. (January 2022) - Crouch, Simone H.; Soepnel, Larske M.; Kolkenbeck-Ruh, Andrea; Maposa, Innocent; Naidoo, Sanushka; Davies, Justine; Norris, Shane A.; Ware, Lisa J.
Summary: Background: The burden of cardiovascular disease (CVD) and hypertension is rapidly increasing in low- and middle-income countries. This is evident not only in adults, but also in children. Recent estimates of prevalence in children are lacking, particularly in Africa. As such, we conducted a systematic review and meta-analysis to provide updated estimates of paediatric hypertension in Africa. Methods: We searched PubMed and EBSCO to identify articles published from January 2017 to November 2020. Studies were assessed for quality. We combined results for meta-analyses using a random effects model (Freeman-Tukey arcsine transformation). Heterogeneity was quantified using the I 2 statistic. Findings: In the narrative synthesis of 53 studies, publication bias was low for 28, moderate for 24, and high for one study. Hypertension prevalence ranged substantially (0·2%-38·9%). Meta-analysis included 41 studies resulting in data on 52918 participants aged 3 to 19 years from ten countries. The pooled prevalence for hypertension (systolic/diastolic BP≥95th percentile) was 7·45% (95%CI 5·30-9·92, I 2 =98.96%), elevated blood pressure (BP, systolic/diastolic BP≥90th percentile and <95th percentile) 11·38% (95%CI 7·94-15·33, I 2 =98.97%) and combined hypertension/elevated BP 21·74% (95%CI 15·5-28·69, I 2 =99.48%). Participants categorized as overweight/with obesity had a higher prevalence of hypertension (18·5% [95%CI 10·2-28·5]) than those categorized as underweight/normal (1·0% [95%CI 0·1-2·6], 4·8% [95%CI 2·9-7·1], p<0·001). There were significant differences in hypertension prevalence when comparing BP measurement methods and classification guidelines. Interpretation: Compared to a previous systematic review conducted in 2017, this study suggests a continued increase in prevalence of paediatric hypertension in Africa, and highlights the potential role of increasing overweight/obesity. Funding: This research was funded in part by the Wellcome Trust [Grant number:214082/Z/18/Z]. LJW and SAN are supported by the DSI-NRF Centre of Human Development at the University of the Witwatersrand.